McGraw-Hill Education GRE 2018 : - Geula, Erfun (McGraw-Hill Education, 2017)
McGraw-Hill Education: Preparation for the GRE Test 2018, Cross-Platform Prep Course covers the foundations of each essential concept, introduces exam strategies, and includes review exercises to help you increase your test-taking confidence.